Physician empathy and patient enablement: survey in the Portuguese primary health care - Simões, José Augusto Rodrigues (2021)
Background: Empathy is the capacity to understand and resonate with the experiences of other people. Patient enablement is the degree to which a patient feels strengthened in terms of being able to deal with, understand and manage their disease. Methods: Secondary cross-sectional analysis of existing data from 2 independent datasets (456 primary health care patients), with the application of two validated questionnaires, Jefferson Scale of Patient Perceptions of Physician Empathy (JSPPPE) and Patient Enablement Instrument (PEI). Objective: Evaluate medical empathy and patients’ enablement after consultation with their family doctors and to verify if there was an association between these two concepts. Results: The median value of JSPPPE-VP score was 6.60 (interquartile range 1.00) and of PEI/ICC score was of 1.83 (interquartile range 0.67). Regarding empathy (JSPPPE-VP), patients taking chronic medication had a slight but significantly higher median score than patients not taking them (6.70 versus 6.60, P = 0.049), although regression modelling did not confirm any relevant predictor of JSPPPE-VP score. Regarding enablement (PEI/ICC), we found significantly higher scores on younger patients, as well as, on more educated and professionally active ones (P < 0.001). Multivariable linear regression and Poisson regression modelling confirmed such variables as statistically significant potential predictors. Conclusions: A significant positive association was found between empathy score (JSPPPE-VP) and enablement score (PEI/ICC), when adjusted to sociodemographic cofactors. On this linear regression model, age category and educational level were also significantly associated with empathy score, with the same pattern found on bivariate analysis.